2008
DOI: 10.1080/10428190802238552
|View full text |Cite
|
Sign up to set email alerts
|

Differences in germinal centre and non-germinal center phenotype in gastric and intestinal diffuse large B-cell lymphomas

Abstract: The gastrointestinal tract is the most common extranodal site of lymphoma, and the most common gastrointestinal lymphoma is diffuse large B-cell type (DLBCL). DLBCL can be separated into germinal centre (GCP) and non-germinal centre phenotypes (non-GCP) using CD10, BCL-6 and MUM1 immunohistochemistry, but primary gastrointestinal DLBCL has not been extensively studied. We investigated 48 cases of primary gastrointestinal DLBCL (33% involving the small intestine, 50% the stomach, 13% the large intestine and 4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
0
16
4
Order By: Relevance
“…Hans et al reported that a combination of CD10, BCL6 and MUM1 expression could subdivide DLBCL patients into long- and short-term survivors [8]. However, contradictory results have been reported on the prognostic role of the Hans classifier [9], [10], [35]. Although non-GCB subgroup was correlated with inferior 5-year OS and PFS in BLBCL, when stratified by treatment non-GCB was only correlated inferior 5-year PFS in the CHOP cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Hans et al reported that a combination of CD10, BCL6 and MUM1 expression could subdivide DLBCL patients into long- and short-term survivors [8]. However, contradictory results have been reported on the prognostic role of the Hans classifier [9], [10], [35]. Although non-GCB subgroup was correlated with inferior 5-year OS and PFS in BLBCL, when stratified by treatment non-GCB was only correlated inferior 5-year PFS in the CHOP cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MUM1 denotes the final step of germinal center B-cell differentiation with subsequent B-cell maturation toward plasma cells (10). A previous report revealed predominance of GCB-like DLBCL in the small intestine, which might be explained by the accumulation of naïve B-cell population in the pre-existing lymphoid tissue such as Peyer's patch (11). In contrast, the present patient showed a non-GCB pattern.…”
Section: Discussioncontrasting
confidence: 52%
“…In primary GI tract DLBCL, the frequency of ABC‐like/ non‐GCB‐like DLBCL was reported to be 42–73 % in the stomach, 6–14 % in the small intestine, and 57 % in the colon . In this study, the frequency of ABC‐like DLBCL was 79 % (19/24) and 58 % (14/24) in the stomach, 70 % (7/10) and 40 % (4/10) in the small intestine, and 60 % (9/15) and 40 % (6/15) in the colon by Choi's and Hans' algorithm, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…The ratio of ABC/ non‐GCB‐like and GCB‐like phenotypes in GI DLBCL varied according to the sites of the GI tract. Specifically, the frequency of ABC/non‐GCB‐like DLBCL was 42–73 % in the stomach, 40 % in the duodenum, 6–14 % in the small intestine, and 57 % in the large intestine …”
mentioning
confidence: 99%